Ecological Ethics and Living Subjectivity in Hegel's Logic - Kisner, W. author. aut Link
X, 337 p.
Keywords: By interweaving Hegelian dialectic and the middle voice, this book develops a holistic account of life, nature, and the ethical orientation of human beings with respect to them without falling into the trap of either subjecting human rights to totality or relegating non-human beings and their habitats to instrumentalism.